Psychological Risk Factors among Transgender: The Mediating Role of Body Dissatisfaction between Quality of Life, Suicidal Ideation and Social Interaction Anxiety: Psychological Risk Factors among Transgender - batool, iram; bakhtawer, sobia; Saher, Noreen; Batool, Huma (South Asian Journal of Social Sciences and Humanities, 2022)
Abstract Social attitudes, prejudice and stigmas towards transgender community vary around the world. Consequently, the prevalence of suicidal attempts, self-injurious behaviors, and associated psychological factors were very common among them. The current study aimed to examine the association between quality of life, suicidal ideation, social interaction anxiety and body image among trans genders. Two hundred trans genders of age between 18-45 years participated in this study. They were approached by using snow ball sampling technique from different cities of Pakistan. Four instruments, Body Image States Scale (BISS), World Health Organization Quality of Life Scale- (WHOQOL-BREF), Beck Scale for Suicidal Ideation (BSSI), Social Interaction Anxiety (SIA) were used in this research. The results showed no significant difference on demographic variables with regard to body image, social interaction anxiety, quality of life and suicidal ideation (p<0.05). Results of mediation analysis by using Smart-PLS showed that body image significantly mediates the association between quality of life and suicidal ideation (r=0.164, p<0.001) and it also mediates the relationship between quality of life and social interaction anxiety (r=0.184, p<0.001). The findings indicated that this population is at a high risk for psychological comorbidities and life-threatening behaviors. Efforts should be taken to reduce discrimination and psychological risk factors and bring positive attitude towards transgender community.